Is the incidence of malignancy increased in patients with sarcoidosis? A systematic review and meta-analysis - Patompong Ungprasert (2018)
© 2014 Asian Pacific Society of Respirology. A possible causal relationship between sarcoidosis and malignancy has been the subject of debates for decades.To better understand this association,we conducteda systematic review and meta-analysisof cohort studies that reported relative risk, hazard ratio or standardized incidence ratio with 95% confidence interval (CI) comparing the incidence of malignancy in patients with sarcoidosis versus non-sarcoidosis participants. Pooled risk ratios (RR) and 95% CI were calculated using a random-effect, generic inverse variance methodology.Five studies were identified and included in our data analyses. The pooled RR of malignancy in patients with sarcoidosis was 1.21 (95% CI: 1.04-1.40). However, when we performed a sensitivity analysis that included only studies that compared the incidence of malignancy after the first year of the diagnosis of sarcoidosis with the incidence of malignancy after the first year of index date for non-sarcoidosis controls, the pooled risk ratio decreased and did not reach statistical significance (RR 1.13, 95% CI: 0.97-1.32). Furthermore, analysis for publication bias has suggested that publication bias in favour of positive studies may be present.In conclusion,after accounting for possible detection bias and publication bias, there does not appear be a significant association between sarcoidosis and malignancy.